2004
DOI: 10.2209/tdcpublication.45.67
|View full text |Cite
|
Sign up to set email alerts
|

Clinical/Photographic Evaluation of a Single Application of Two Sealants After Eleven Years

Abstract: The clinical behavior of Concise and Prisma Shield sealants for pit and fissure was analyzed by clinical/photographic evaluation. A hematoxylin-based staining solution was applied to the occlusal surface 7 days, 18 months, 36 months, and 11 years after the occlusal sealing, thus allowing the sealant material on the surface to be checked. At each analysis time, each occlusal surface was photographed, and the photographs corresponding to each time were submitted to clinical/photographic evaluation. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
1
15
1
4
Order By: Relevance
“…Acid etching of dental enamel prior to application of a resin material considerably influences the durability of that material in the oral cavity. One such example is the accomplishment of pit and fissure sealants reported by Simonsen in 1991 17) and Sundfeld et al in 2004 19) , at 15 and 11 years after application, respectively. This was mainly due to the extremely accurate technique to which the sealing material was submitted, comprising application on etched, well-dried, and non-contaminated enamel.…”
Section: Resultsmentioning
confidence: 99%
“…Acid etching of dental enamel prior to application of a resin material considerably influences the durability of that material in the oral cavity. One such example is the accomplishment of pit and fissure sealants reported by Simonsen in 1991 17) and Sundfeld et al in 2004 19) , at 15 and 11 years after application, respectively. This was mainly due to the extremely accurate technique to which the sealing material was submitted, comprising application on etched, well-dried, and non-contaminated enamel.…”
Section: Resultsmentioning
confidence: 99%
“…This method is a clinically conservative, non-traumatic, biocompatible means by which resins, polymerizable under oral conditions, can be bonded durably to enamel 6) . In addition, the success of acid etching of enamel prior to the placement of adhesive materials has had a profound effect on the long-term behavior of those materials in the oral cavity 12,18) . It has been observed that when teeth with composite resin restorations are bleached, a color discrepancy is created which frequently requires the replacement of existing restorations 1,7,10,11,[13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Alguns fatores são fundamentais para assegurar a retenção deste material na superfície dentária: morfologia das fossas e fissuras, propriedades físico-químicas do esmalte dentário, grau de limpeza da superfície dentária, viscosidade do material usado como selante e qualidade na técnica de aplicação [11][12][13][14][15][16] . O cuidado com a técnica merece destaque, na medida em que cada etapa do protocolo deve ser rigorosamente executada.…”
Section: Introductionunclassified
“…O cuidado com a técnica merece destaque, na medida em que cada etapa do protocolo deve ser rigorosamente executada. Exige-se que a superfície dentária esteja limpa, livre de umidade e adequadamente preparada para receber o material indicado para o selamento das fossas e fissuras [14][15][16] . Estes aspectos devem ser enfatizados aos estudantes e jovens profissionais, para que o protocolo seja executado com o máximo cuidado, evitando imperfeições que possam comprometer a longevidade do selamento.…”
Section: Introductionunclassified